Purkinje cell (PC) antibody positivity in a patient with autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy. (15th September 2022) - Xu, Li; Xian, Wenbiao; Li, Jin; Yao, Xiaoli; Long, Youming
Abstract: Purpose: This case report is the first to describe the detection of antibodies against inositol 1, 4, 5-trisphosphate receptor 1 (ITPR1, I3PR) in a patient diagnosed with autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy. ITPR1 is known as one of the Purkinje cell antibodies present in autoimmune cerebellar ataxia (ACA). Here, we described the association between autoimmune GFAP astrocytopathy and autoimmune cerebellar disease (ACD). Materials and methods: Demographic features, clinical characteristics, cerebrospinal fluid (CSF) parameters and neuroimaging findings were collected from this patient. Specifically, antibodies against GFAP and other proteins associated with neurological disorders were measured by immunofluorescence staining in both serum and CSF samples. Results: A 52-year-old woman was diagnosed with autoimmune inflammatory meningoencephalitis. She presented with cognitive dysfunction, psychiatric/behavioral abnormalities and serious insomnia with subacute onset. Brain magnetic resonance imaging (MRI) showed bilateral hyperintensity in the semioval centers on axial images and perivascular linear enhancement oriented radially to the ventricles on sagittal images. GFAP-IgG, oligoclonal bands (OBs), N-methyl-D-aspartate receptor (NMDAR)–IgG and ITPR1-IgG co-existed in her CSF. She responded well to immunoglobulin and steroid treatments. Conclusion: Here, we describe the case of a patient with autoimmune GFAP astrocytopathy whose CSF was positive for ITPR1-IgG; however, she did not show typical ataxia manifestations or cerebellar lesions on her MRI scan. This suggests that ITPR1-IgG is not pathogenic, and the positivity of this antibody in CSF is probably associated with the presence of autoimmune inflammation.